Uninvited Guests: The Influence of Teachers' Roles and Pedagogies on the Positioning of English Language Learners in the Regular Classroom - Yoon, Bogum (American educational research journal, 2008)
Grounded in positioning theory, this study examined regular classroom teachers' views of their roles with regard to English language learners (ELLs) and the relationship between their teaching approaches and the students' reactions and positioning of themselves in the classroom. Findings suggest that the teachers' views of their roles varied based on their positioning of themselves as teachers for all students, as teachers for regular education students, or as teachers for a single subject. The teachers' different approaches were related to the ELLs' different levels of participation and their positioning of themselves as powerful or powerless students. The study breaks important ground in our understanding of the complex interactional classroom dynamics that influence the teaching and learning of ELLs.